Preoperative serum albumin as a prognostic factor in patients with upper urinary tract urothelial carcinoma - Ja Hyeon Ku (International Brazilian Journal of Urology, 2014)
Purpose The study evaluated whether preoperative measures of the C-reactive protein-based systemic inflammatory response may predict cancer survival independent of tumor stage in patients with upper urinary tract urothelial carcinoma (UTUC). Materials and Methods Between September 1999 and October 2010, 181 patients submitted to radical nephroureterectomy were available for evaluation. Multivariate survival analyses were performed using Cox’s proportional hazards model and the coefficient for each factor was divided by the highest coefficient, multiplied by 4, and rounded to the nearest integer. Results Multivariate analyses showed that tumor location, pathologic T stage, lymphovascular invasion, margin status, and albumin level were independent contributors. The bootstrap-corrected C statistics of the model were 0.813 for disease-specific survival and 0.755 for overall survival, respectively. For time to disease-specific and overall mortality for patients, integrated area under the curve values were 0.792 and 0.739, respectively. When patients were clustered into three groups according to their model-predicted survival, the 5-year disease-specific survival in the low-, intermediate- and high-risk group was 95.4%, 76.2%, and 36.9%, respectively (p<0.001), and were 87.8%, 54.4%, and 31.8%, respectively, for overall survival (p<0.001). Decision curve analysis revealed that the use of model was associated with net benefit gains relative to the treat-all strategy. Conclusions   Pretreatment albumin is a simple biomarker based on routinely available well-standardized measures, and is not an expensive and time-consuming process. Hypoalbuminemia is an independent marker of poor prognosis in patients with upper urinary tract urothelial carcinoma.